Directive and Expressive Speech Acts in Nadine Labaki's Capernaum (A Pragmatic Study) - Ifaqoh, Hanifah Insani; Su'aidi, Agus Ahmad (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2023)
This research is intended to present the forms and functions of directive speech acts and expressive speech acts. This research is entitled